(untitled) (ELS Journal on Interdisciplinary Studies in Humanities, 2025)
Cohesion and coherence are essential components in academic writing which bridge an academia to create logically organized text and easy to comprehend. Thus, this research aims to identify the use of cohesion and coherence devices in the background section of Skripsi written by students of the English Education Study Program of Tadulako University. This research employs a mixed-method, which involves quantitative and qualitative analysis. The data were taken from ten selected Skripsi backgrounds. The findings of this research present that the most frequently used of cohesive devices is reiteration (48.09%), followed by reference (32.20%), and conjunction 1(9.49%). In contrast, the least frequently used cohesive devices are substitution and ellipsis, each appearing only (0.11%). Furthermore, in terms of coherence, the students dominantly implement repeat key nouns (66.27%), followed by consistent pronouns (22.88%), transition signals (8.88%), and logical order (1.97%). Although some devices appeared less frequently, the students’ academic writing still achieved overall textual unity and logical flow. Therefore, these findings indicate that while students have good abilities to build cohesion and coherence in their writing, there remains need to encourage more varied use of devices, particularly substitution, ellipsis, and transition signal, in order to further improve their quality of academic writing.